(untitled) (Kanun: Jurnal Undang-undang Malaysia, 2016)
The tragedy of flight MH370 belonging to Malaysia Airlines (MAS) that went missing on 8 March 2014 en route from Kuala Lumpur to Beijing has become a global issue, gaining attention all over the world. The mystery of the still- missing plane has opened a new chapter in assessing the status of al-mafqud (missing person) under shariah law. The disappearance of the passengers and crew members on board has placed Islamic financial institutions, especially takaful operators, in a difficult position with respect to meeting the claims of the heirs if the al-mafqud due to inavailability of evidence to confirm the death of the passengers and crew members of MH370. Takaful operators have to seek the views from their respective Shariah committees in order to determine whether the takaful benefits should be paid or not, and if these are to be paid, which fund should be used pay them: the takaful operators’ shareholders’ fund or the participants’ risk fund (tabaruk fund). This paper highlights the basic applications of fiqh al-mafqud in connection with the MH370 tragedy, as well as its implications for the takaful industry. Keyword:al-mafqud, missing person, presumption of death, MH370,National Fatwa Council